Mechanistic investigation of Rh(i)-catalysedasymmetric Suzuki–Miyaura coupling withracemic allyl halides - Van Dijk, LL; Ardkhean, R; Sidera, M; Karabiyikoglu, S; Sari, Ö; Claridge, T; Lloyd-Jones, G; Paton, R; Fletcher, S (Nature, 2021)
Understanding how catalytic asymmetric reactions with racemic starting materials can operate would enable new enantioselective cross-coupling reactions that give chiral products. Here we propose a catalytic cycle for the highly enantioselective Rh(I)-catalysed Suzuki–Miyaura coupling of boronic acids and racemic allyl halides. Natural abundance 13C kinetic isotope effects provide quantitative information about the transition-state structures of two key elementary steps in the catalytic cycle, transmetallation and oxidative addition. Experiments with configurationally stable, deuterium-labelled substrates revealed that oxidative addition can happen via syn- or anti-pathways, which control diastereoselectivity. Density functional theory calculations attribute the extremely high enantioselectivity to reductive elimination from a common Rh complex formed from both allyl halide enantiomers. Our conclusions are supported by analysis of the reaction kinetics. These insights into the sequence of bond-forming steps and their transition-state structures will contribute to our understanding of asymmetric Rh–allyl chemistry and enable the discovery and application of asymmetric reactions with racemic substrates.